An orange‐emitting phosphor BaSrGa4O8:Bi3+, K+ with unique one‐dimensional chain structure for high index color WLEDs. Issue 11 (6th August 2020) - Hu, Songhan; Long, Zhangwen; Wen, Yugeng; Qiu, Jianbei; Zhou, Dacheng; Lai, Jun'an; Wang, Dazhao; Pi, Jiacheng; Li, Xizheng; Wang, Qi
Abstract: It has been an urgent need for developing a new bright long‐wave emitting phosphor to improve the color rendering index (CRI) of white light‐emitting diodes (WLEDs). Here, based on the concept of oxygen vacancy‐induced long‐wave emission by Bi 3+ doping, we selected BaSrGa4 O8 as the matrix, which has a low‐dimensional chain structure that can produce enough oxygen vacancies. After the introduction of Bi 3+, orange emission was successfully achieved. To further improve the luminescence efficiency, the system of BaSrGa4 O8 :Bi 3+, K + was designed. Interestingly, although significant emission enhancement was obtained, the material showed reduced absorption with increased oxygen vacancies. More detailed experimental evidences confirm that oxygen vacancies can activate Bi 3+ to achieve long‐wave emission. Our results provide a new way to design Bi 3+ ‐based long‐wave emitting phosphors with low‐dimensional crystal structure. Finally, a WLED device containing BaSrGa4 O8 :Bi 3+, K + was fabricated and exhibited an enhanced CRI, which shows a promising application in WLEDs. Abstract : After potassium ions got into the lattice, more oxygen vacancies can be produced, leading to the enhanced Bi 3+ splitting. This behaviour increased the intensity of photoluminescence for a significant enhancement of orange‐red light emission.